Rekindling the Lasallian spirit: A program report - Laxa, James B. (Animo Repository, 2012)
Rekindling the Lasallian Spirit is a program that addresses the need to form, nourish, and sustain faith communities in the university. As a university that seeks to bridge faith and scholarship, and integrate faith and life, the program is an avenue for faith development and the enrichment of our Lasallian community. The program takes place through spiritual-oriented activities in the departments and offices. The program intends to stimulate participants towards a desire to participate in activities geared towards enhancing individual spiritual lives while building small faith communities in the process. Observations and qualitative evaluations have indicated a positive reception to the program.